Anesthetic Management of Wilms’ Tumor Patient Using Thoracal Epidural Block: A Case Report - Tenggara, Alamsyah; Dewa Ayu Mas Shintya Dewi (Journal of Anesthesiology and Clinical Research, 2023)
Introduction: Wilms’ tumor or nephroblastoma is an embryonal tumor that develops from the remaining immature kidney and is the fourth most common primary renal tumor malignancy in children. An asymptomatic abdominal mass is present in more than 90% and hematuria in 30% of patients. Preoperative workup includes complete laboratory blood tests and imaging to ensure intrarenal mass. This study aimed to describe the anesthetic management of Wilms’ tumor patients. Case presentation: A two-year-old girl was diagnosed with Wilms' tumor with the main complaint of intermittent hematuria. An abdominal CT scan showed an enlargement mass in the right kidney with a size of +/- 7.4 x 5.9 x 9.5 cm. The patient was planned for radical nephrectomy. In addition to general anesthesia, an epidural catheter is placed at the 10th-11th thoracic level (T10-T11). Conclusion: Epidural placement in pediatrics undergoing abdomen surgery have various beneficial considerations, such as superior analgesia, minimal opioid use, reduced intraoperative bleeding, and decreased postoperative ventilator requirements.